Potentials of rose (Rosa damascena) petals and receptacles extract as antioxidant and antihyaluronidase - Desi Yustra Sari Dewi; Chrismis Novalinda Ginting; Linda Chiuman; Ermi Girsang; Rr. Anisa Siwianti Handayani; Wahyu Widowati (Pharmaciana, 2020)
Free radicals affect aging by unspecific lead breakdown to macromolecules, like DNA, lipids, and proteins. The degradation of the extracellular matrix affects skin aging and correlated with the hyaluronidase enzyme. Rose (Rosa damascena) petal extract and rose receptacle extract can scavenge free radicals, thus hindering the aging process. This study examines phenolic and flavonoid content, the antioxidant, anti-hyaluronidase potential owned by rose petal extract (RPE), and rose receptacle extract (RRE) inhibiting skin aging. In this study, Hydrogen peroxide (H2O2) scavenging activity assay was done to analyze the antioxidant activity while the hyaluronidase inhibitory assay analyzed antiaging activity. The characteristic of RPE and RRE were measured the phenolics and flavonoids content. The phenolics content of  RPE and RRE were 9.66 μg GAE/mg RPE and  4.31  μg GAE/mg RRE, respectively, while the flavonoids content of  RPE and RRE respectively 1.22 μg QE/mg RPE and 0.59 μg QE/mg RRE. The median inhibitory (IC50) of H2O2 scavenging of RPE (207.99 µg/mL) was more active than RRE (348.24 µg/mL). RPE's anti-hyaluronidase (IC50: 51.68 µg/mL) is as effective as RRE (IC50: 51.98 µg/mL). Antioxidant and antiaging activities possessed by RPE and RRE are promising natural agents for aging therapy.